Pengaruh Penambahan Kalium Ferosianida Pada Pembuatan Asam Sitrat Dari Tetes Secara Fermentasi - Karsini Karsinir (Balai Besar Kimia dan Kemasan, 1989)
Molases the by-product of sugar mild, usually contain metal ions mainly Fe, Zn, Cu and Mn.In the citric acid making process, low concentration of these ions do help the micellium growth, however the high concentration of these metal ions will cause an uneffective fermentation process. The use of potasium ferocyanide in the treatment of molasses, which is one way to reduce this negative effect, is being reviewed.